The search for efficient diagnostic and prognostic biomarkers of heart failure. (May 2016) - Emdin, Michele; Mirizzi, Gianluca; Pastormerlo, Luigi E; Poletti, Roberta; Giannelli, Elena; Prontera, Concetta; Passino, Claudio; Vergaro, Giuseppe
Several biomarkers have been tested for screening, diagnosis and prognosis purposes, as well as to guide treatment in heart failure, but only the assay of circulating B-type natriuretic peptides has widely recognized applications for clinical decision-making. Natriuretic peptides are sensitive in detecting the clinically overt or subclinical myocardial damage, but their plasma levels are increased following every generic insult to the cardiovascular system. Novel biomarkers are required to identify specific pathways of disease progression, such as diverse neurohormonal axes activation, inflammation and fibrogenesis, and to act as a tool for therapeutic tailoring. In this view, Gal-3 and ST-2 assays seem very promising, given their involvement in mechanisms of cardiac fibrosis and their prognostic value.